PROFIL DAMPAK POSITIF DAN NEGATIF PENGGUNAAN HANDPHONE PADA PESERTA DIDIK KELAS X DI SMA NEGERI 12 PEKANBARU - Resmita Widya Ningsih; Elni Yakub; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was conducted in SMA Negeri 12 Pekanbaru. This research entitled "Profile of Positive and Negative Impact of Handphone Usage on Class X Student in SMA Negeri 12 Pekanbaru". The purpose of this research is to know the picture of positive and negative impacts of handphone usage on learners. Data collection tools include systematic non-participatory observation and open interviews. Subjects used in this study amounted to five people. Consideration or basic researcher to take the subject of the students who use the phone with the duration of time ranging from 17 to 19 hours in 24 hours, while at school and at home. This is based on assessments from researchers, from BK teachers and from the assessment of subject friends at school. Analysis of data that researchers do is qualitative which is described with words or sentences separated by category to draw conclusions. Research conducted found that the positive impact of the use of mobile phones by learners is easier to communicate, improve social fabric and relieve stress. The negative impact of the use of mobile phones by learners is to make students lazy to learn, interfere with the concentration of student learning, forget the duties and obligations, disrupt the development of children, potentially affecting attitudes and behavior, and waste.Keywords: Impact, Handphone Usage, Student